Posted by **sh** on Wednesday, November 4, 2009 at 5:20pm.

Differentiate using the chain rule:

y=(x+(x+x^(1/2))^(1/2))^(1/2)

y'=(1/2)(x+(x+x^(1/2))^(1/2))^-(1/2)

what are the next steps?

## Answer this Question

## Related Questions

- Calculus - I'm having problems with this one. Can't get the right answer. ...
- calculus - Using the chain rule... how can i differentiate this? y=x(x-2)
- calculus - I have been asked to solve this two different ways. The first way is...
- calculus - I am having trouble with this problem also derivative differentiate f...
- calculus 1 - differentiate x(x-3)^2 do I product and chain rule?
- calculus help - implicit differentation 1.y^3=4(x^2+y^2) 2.y^2-3x+2y=0 help ...
- maths - differentiate using product, chain and quotient rule ln x / 5x-7 and e^x...
- Calculus - How do I use the chain rule to find the derivative of square root(1-x...
- calculus - Thank you Reiny for replying.I know names have changed. Perhaps I ...
- Calculus - Differentiate: y=ln(x/(2x+3))^(1/2) y=(1/2)ln(x/(2x+3)) y'=0+(1/2)((...